Santripreneur Education Model Based On The Maqashid Al-Syariah Framework For The Economic Empowerment Of Santri In Pesantren - Rohim, Yasin Nur; Pratama, Bagas Brian (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This study aims to design a santripreneur education model based on the Maqashid Al-Syariah framework as a strategic effort to empower the economy of santri in Pesantren. The novelty of this study lies in the integration of the five main dimensions of Maqashid Al-Syariah—Hifdzu Ad-Diin, Hifdzu An-Nafs, Hifdzu Al-Aql, Hifdzu An-Nasl, and Hifdzu Al-Maal—into the entrepreneurship education curriculum, which has not been widely studied in depth in the context of Pesantren in Indonesia. The research method uses a descriptive qualitative approach with a scoping review strategy, to map the literature related to the santripreneur education model and the values of Maqashid Al-Syariah. The results show that this model is able to shape santri as Muslim entrepreneurs who are not only oriented towards financial gain, but also uphold ethical values, social responsibility, and business sustainability according to sharia principles. The relevance of this model is increasingly strong in addressing the economic challenges of Pesantren, as well as supporting the achievement of santri's spiritual and economic independence in the long term.